Progress in Understanding Ferroptosis and Its Targeting for Therapeutic Benefits in Traumatic Brain and Spinal Cord Injuries - Hu, Xinli; Xu, Yu; Xu, Hui; Jin, Chenqiang; Zhang, Haojie; Su, Haohan; Li, Yao; Zhou, Kailiang; Ni, Wenfei (Frontiers in Cell and Developmental Biology, 2021)
Acute central nervous system (CNS) trauma, including spinal cord injury (SCI) and traumatic brain injury (TBI), always leads to severe sensory, motor and autonomic nervous system dysfunction due to a series of processes, including cell death, oxidative stress, inflammation, and excitotoxicity. In recent years, ferroptosis was reported to be a type of programmed cell death characterized by the consumption of polyunsaturated fatty acids and the accumulation of membrane lipid peroxides. The processes that induce ferroptosis include iron overload, imbalanced glutathione metabolism and lipid peroxidation. Several studies have indicated a novel association of ferroptosis and acute CNS trauma. The present paper reviews recent studies of the occurrence of ferroptosis, stressing the definition and process of ferroptosis and metabolic pathways related to ferroptosis. Furthermore, a summary of the existing knowledge of the role of ferroptosis in CNS trauma is presented. The aim here is to effectively understand the mechanisms underlying the occurrence of ferroptosis, as well as the relevant effect on the pathophysiological process of CNS trauma, to present a novel perspective and frame of reference for subsequent investigations.